ChemInform Abstract: Homogeneous Catalytic Processes Monitored by Combined in situ ATR‐IR, UV‐Vis, and Raman Spectroscopy. Issue 33 (19th August 2014) - Grabow, Kathleen; Bentrup, Ursula
Abstract Review: 57 refs.